L-Acetylcarnitine causes analgesia in mice modeling Fabry disease by up-regulating type-2 metabotropic glutamate receptors. (23rd March 2022) - Formaggio, Francesco; Rimondini, Roberto; Delprete, Cecilia; Scalia, Leonardo; Merlo Pich, Emilio; Liguori, Rocco; Nicoletti, Ferdinando; Caprini, Marco
Fabry disease (FD) is a X-linked lysosomal storage disorder caused by deficient function of the alpha-galactosidase A (α-GalA) enzyme. α-GalA deficiency leads to multisystemic clinical manifestations caused by the preferential accumulation of globotriaosylceramide (Gb3). A hallmark symptom of FD patients is neuropathic pain that appears in the early stage of the disease as a result of peripheral small fiber damage. Previous studies have shown that Acetyl-L-carnitine (ALC) has neuroprotective, neurotrophic, and analgesic activity in animal models of neuropathic pain. To study the action of ALC on neuropathic pain associated with FD, we treated α-GalA gene null mice (α-GalA(-/0)) with ALC for 30 days. In α-Gal KO mice, ALC treatment induced acute and long-lasting analgesia, which persisted 1 month after drug withdrawal. This effect was antagonized by single administration of LY341495, an orthosteric antagonist of mGlu2/3 metabotropic glutamate receptors. We also found an up-regulation of mGlu2 receptors in cultured DRG neurons isolated from 30-day ALC-treated α-GalA KO mice. However, the up-regulation of mGlu2 receptors was no longer present in DRG neurons isolated 30 days after the end of treatment. Taken together, these findings suggest that ALC induces analgesia in an animal model of FD by up-regulating mGlu2 receptors, and that analgesia is maintained by additional mechanisms after ALC withdrawal. ALC might represent a valuable pharmacological strategy to reduce pain in FD patients.